Microscopy and surface chemical investigations of dyed cellulose textiles - Chettra, Satinderjeet Kaur (2006)
Cotton is a vital material for the textile industry, providing the fundamental raw component for the manufacture of numerous and varied garments. It has been thoroughly characterised both in terms of its constitution; behaviour under a variety of environmental and manufacturing conditions; and several mechanisms by which it takes up dyestuffs. Recently the availability of a range of high-performance surface analysis tools has allowed researchers to begin to assess the contribution of the surface interface to the overall properties of cellulose in cotton. In particular, these approaches offer considerable potential to address the current lack of fundamental experimental data in support of the proposed dye-uptake mechanisms in cotton fibres. The absence of a detailed molecular model for the process makes it difficult to predict dye performance and to identify the key characteristics of the cotton which influence dyeing. For example, the existence and location of dye binding sites is still unclear. It has been postulated that the occurrence of crystalline or amorphous regions in cotton may play a role in such binding and in dye uptake. A deeper understanding of the dyeing mechanisms therefore requires knowledge of the interplay between the physical chemistry of the dye, its adsorption/diffusion onto the surface of and within cotton fibres, and the related physical and chemical characteristics of the cotton itself. Here we begin to address these broad questions through the application of atomic force microscopy (AFM) and other complimentary surface analytical techniques, to analyse a range of dyed and undyed cellulose based textiles. We provide high-resolution surface morphological image data, which show nanometre scale detail of the surface of dyed and undyed cotton fibres. It is believed that the dyeing process induces an increase in crystallinity, due to breakages in hydrogen bonds between cellulose chain molecules during swelling of fibres within the dyebath, thus allowing dye molecules to enter and become entrapped within the fibre matrix. We provide evidence in the form of image data that suggest a difference in the crystal structure between undyed and dyed cellulose fibres to support this theory. We also reveal possible crystalline and amorphous regions within the substrate through AFM phase imaging using modified tips and successfully fingerprint regions of dyed and undyed cellulose fibres. Complimentary surface chemical analysis of dyed and undyed fibres, provide qualitative and quantitative data to show the presence of dye molecules on the surface of dyed cellulose textiles. Novel investigations of dyed fibres through X-ray photoelectron spectroscopy (XPS), determine the amount of dye present at the surface of cotton fibres. Using the N 1s atomic orbital region as a diagnostic peak, the level of dye loading could be directly attributed to the concentration levels of dye within the dyebath. The XPS data also provided strong evidence for possible dye-uptake mechanisms. We observed that certain stages of the dyeing process directly influenced the amount of dye entering cotton fibres. XPS showed that an increase in salt (NaCl) content within the dyebath produced dyed fibres with increased presence of dye compound at the surface. The knowledge obtained from these studies will help to improve the dyes and dyeing mechanisms for cotton and other textiles, thus improving the quality of dyed garments offered to the consumer.